A clinical case of a young patient with post-myocarditis atrial fibrillation and heart failure with reduced ejection fraction - Liudmila, Kalatsei; Kokwewa, R. B. S. W. M. Pasan M.; Gawarammana, M. M. Shalini P. (International Journal of Research in Medical Sciences, 2025)
A clinical observation of a 26-year-old patient with post-myocarditis atrial fibrillation and heart failure (HF) with reduced left ventricular ejection fraction (LVEF) is presented. In February 2025 the patient suffered from acute myocarditis, diagnosed based on magnetic resonance imaging. The outcome was post-myocarditis cardiosclerosis complicated by HF with LVEF 28%, followed by hospitalization in a cardiology hospital. During treatment, quadruple therapy (angiotensin receptor and neprilysin inhibitor, beta-blocker, mineralocorticoid receptor antagonist, sodium-glucose cotransporter type 2 inhibitor) was initiated and sinus rhythm was restored by electrical cardioversion. This therapeutic approach resulted in significant improvements, including a regression of congestive symptoms, a natriuretic peptide level from 2530 to 267 pg/ml, and an increase in LVEF from 28% to 65%. This clinical case highlights the complexity of not only the timely diagnosis of myocarditis but also the treatment of its consequences.